2022
DOI: 10.5539/ach.v14n1p6
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Personal Finances in the Academic Curricula: A Critical Analysis of Their Potential Synergies

Abstract: The research addresses two major topics, Emotional Intelligence and Personal Finance, and the need to be permanently included in the academic curricula. The purpose of the paper consists in raising awareness within the teaching community on the relevance of these two topics for the personal and professional development of students. Furthermore, the research identifies the potential positive synergies between emotional intelligence and personal finances for students when both subjects are included in the academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Similar results were obtained in other studies. It was shown that EI allows effective management of finances both on a personal and professional level (Imam et al, 2022). Emotional awareness and emotional confidence lead to informed decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained in other studies. It was shown that EI allows effective management of finances both on a personal and professional level (Imam et al, 2022). Emotional awareness and emotional confidence lead to informed decisions.…”
Section: Discussionmentioning
confidence: 99%
“…It allows building effective interaction, which has a productive effect on the results of financial activities (Istianingsih et al, 2020). At the same time, the lack of EI skills can lead to incorrect financial decisions, which reduces financial success (Imam et al, 2022).…”
Section: Introductionmentioning
confidence: 99%